Management of Symptomatic Mesenchymal Hamartoma of the Chest Wall: Surgical Resection Only in Symptomatic Cases - Virgone, C.; Dall’Igna, P.; Alaggio, R.; Burnelli, R.; Zanon, G. F.; Cecchetto, G. (Klinische Pädiatrie, 2013)
Mesenchymal hamartoma of the chest wall (MHCW) is a rare neonatal benign tumor with an estimated incidence of 1 in 3 000 among primary bone tumors, and 1 in one million in the general population. Traditionally, the treatment of choice was an “en bloc” resection, but surgery limited to symptomatic cases, is now suggested by most authors due to the numerous cases of spontaneous regressions. We report 2 patients of symptomatic MHCW, characterized by progressive respiratory distress, who underwent surgical treatment with prompt resolution of symptoms. Surgeons and neonatologists should be aware of this rare condition and its possible fatal or nearly-fatal complications.
Keywords: mesenchymal chest wall hamartoma; benign soft-tissue tumors; thoracic tumors; neonatal tumors